LIFE SKILL MENJAHIT OLEH WANITA DI DESA SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Devi Agustinah; Daeng Ayub; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the Life Skill of Tailoring by Women in Sungai Segajah Village, Kubu District, Rokan Hilir Regency. The formulation of the problem of this research is what kind of parenting is applied by oil palm farmers in educating their children ?, How high is the indicator contribution to the Life Skill Tailoring variable? This research consists of 4 indicators, according to the opinion of Syamsul Kurniawan. The sample of this study used the Simple Random Sampling technique, because the sampling of members of the population was carried out randomly without regard to strata in the population. How to do this if the population members are considered homogeneous, (Sugiyono, 2011: 57). Data collection techniques, documentation, observation, interviews and questionnaires, totaling 35 statements. Data obtained from respondents totaling 20 people for the trial sample and 40 people for the study sample. After the questionnaire was tested, there were 5 statements and the researchers threw out invalid statements. Based on the mean value of the variable Life Skill Tailoring by Women in Sungai Segajah Village, Kubu District, Rokan Hilir Regency is relatively high with a mean value of 4.41 and SD 0.16. The interpretation obtained for each indicator of Life Skill Tailoring by Women in Sungai Segajah Village, Kubu District, Rokan Hilir Regency is classified as high, except the Life Skill Tailoring indicator of Vocational Skills is very high. So, seen the most dominant of these 4 indicators is vocational skills.Key Words: Life Skills for Tailoring by Women